Screening Of α-Amylase Inhibitor Rhodomyrtus tomentosa (Aiton) Hassk. By Docking Method - samsul hadi (Science Midwifery, 2021)
Diabetes cases in Indonesia are increasing along with economic growth and people’s welfare, so the use of oral drugs for diabetes mellitus is also increasing. One of the drugs used is acarbose, this drug works as an α-amylase inhibitor. With the increasing use of drugs causing side effects on the body, it is necessary to screen natural ingredients for alternative treatments of diabetes mellitus. The natural ingredient used in this research is R. tomentosa. The docking method used to find interaction stability is pyrex. The result of this research are alpha-Tocopherol quinone (-5,1 kcal/mol); blumeatin (-7,3 kcal/mol); methyl cinnamate (-5,1 kcal/mol); myricetin (-7,7 kcal/mol); naringenin (-7,0 kcal/mol); quercetin (-7,5 kcal/mol); rhodomyrtone (-7,4 kcal/mol); rhodomyrtosone B (-7,3 kcal/mol); rhodomyrtosone C (-8,8 kcal/mol); tetrahydroxyflavanone (-7,2 kcal/mol); tocopherol A (-7,8 kcal/mol); and verimol K (-6,4 kcal/mol). Based on the screening of R. tomentosa content as an α-amylase inhibitor using the docking method, it can be concluded that the compound which has interaction stability is rhodomyrtosone C